2020
DOI: 10.1186/s12879-020-05582-7
|View full text |Cite
|
Sign up to set email alerts
|

Infected aortic aneurysm caused by Helicobacter cinaedi: case series and systematic review of the literature

Abstract: Background Helicobacter cinaedi is rarely identified as a cause of infected aneurysms; however, the number of reported cases has been increasing over several decades, especially in Japan. We report three cases of aortic aneurysm infected by H. cinaedi that were successfully treated using meropenem plus surgical stent graft replacement or intravascular stenting. Furthermore, we performed a systematic review of the literature regarding aortic aneurysm infected by H. cinaedi. Case presentation We present three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 38 publications
0
18
0
4
Order By: Relevance
“…Infected aortic aneurysms caused by H. cinaedi are increasingly being recognized, especially in Japan, although the detection rate remains low ( 3 ). One study reported 734 cases of infected aortic aneurysms caused by various organisms, including Salmonella , Staphylococcus , Streptococcus , and Escherichia coli , but not H. cinaedi ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infected aortic aneurysms caused by H. cinaedi are increasingly being recognized, especially in Japan, although the detection rate remains low ( 3 ). One study reported 734 cases of infected aortic aneurysms caused by various organisms, including Salmonella , Staphylococcus , Streptococcus , and Escherichia coli , but not H. cinaedi ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because nonsurgical treatment has been shown to be effective, open surgery during the acute phase of infection might be overindicated. Endovascular stent grafting, a less invasive treatment than the standard vascular replacement procedure, followed by use of appropriate antimicrobial agents might successfully complete treatment ( 3 ). This treatment is beneficial among aging patients, and it is hoped that the presence of these bacteria in infected aortic aneurysms will be widely recognized, with treatment and diagnosis proceeding simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 The following etiologic agents have been reported: gram-positive bacteria such as Staphylococcus sp. , 2 , 4 , 6 - 8 , 11 , 14 , 19 Enterococcus sp. , 11 Streptococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…, 11 Streptococcus sp. 2 , 8 , 11 , 18 , 19 and Clostridium sp. , 11 and gram-negative bacteria such as Salmonella sp.…”
Section: Discussionmentioning
confidence: 99%